Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s10584-006-9217-0
|View full text |Cite
|
Sign up to set email alerts
|

On interpreting hydrological change from regional climate models

Abstract: Although representation of hydrology is included in all regional climate models (RCMs), the utility of hydrological results from RCMs varies considerably from model to model. Studies to evaluate and compare the hydrological components of a suite of RCMs and their use in assessing hydrological impacts from future climate change were carried out over Europe. This included using different methods to transfer RCM runoff directly to river discharge and coupling different RCMs to offline hydrological models using di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
199
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(215 citation statements)
references
References 44 publications
11
199
0
3
Order By: Relevance
“…Finally, the whole area has been subjected to very intense socio-political debate because of the National Water Plan, which proposes to transfer water from inland in the north to the south (from the EBR to the JUC, and SEG hydrological divisions). Therefore, it can be seen once again that changes in mountain or remote areas can affect distant populations (Barnett et al, 2005;Graham et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the whole area has been subjected to very intense socio-political debate because of the National Water Plan, which proposes to transfer water from inland in the north to the south (from the EBR to the JUC, and SEG hydrological divisions). Therefore, it can be seen once again that changes in mountain or remote areas can affect distant populations (Barnett et al, 2005;Graham et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the choice of GCM in providing boundary conditions for RCMs plays a larger role in hydrological change than the choice of emissions scenario. Graham et al (2007b) used the same models to obtain estimates of hydrological change for river basins in northern and central Europe. Here, RCMs were able to reproduce the seasonal cycle of precipitation but most overestimated precipitation amounts.…”
Section: Use Of Multiple Model Outputs and Emissions Scenariosmentioning
confidence: 99%
“…Grams et al, 2014). For applications at smaller scales RCM output may be preferable, but the quality of the RCM output may still largely depend on the performance of the driving GCM (Graham et al, 2007). Coupling to impact models is not part of our study, yet we choose to conduct the evaluation for river basins in the hope that our results will prove informative for such future applications.…”
Section: Introductionmentioning
confidence: 99%